Analisis Pengaruh Partisipasi Masyarakat, Kompetensi dan Sistem Pengendalian Internal Terhadap Akuntabilitas Pengelolaan Dana Desa - Risnalamelan Agifirilarani; Ardiansyah Japlani; Karnila Ali (Jurnal Manajemen DIVERSIFIKASI, 2026)
This research aims to examine the influence of Community Participation, Competence and Internal Control Systems on Accountability in Village Fund Management. This research uses financial management theory. The data used in this research is primary data based on questionnaires distributed to village officials and the community. This research method uses a sample of village officials who work at the Gedung Gumanti Village Subdistrict Office. The sample in this research is 30 people, based on a purposive sampling method, namely officials who have a minimum of SMP/MTS degree and have worked for more than one year. The choice of hypothesis testing in this research uses multiple linear regression. The results of this research show that Community Participation and the internal control system have a positive effect on Village Fund Management Accountability, while Competency also has a positive effect on Village Fund Management Accountability.